Comparative Distribution of Relaxin-3 Inputs and Calcium-Binding Protein-Positive Neurons in Rat Amygdala - Santos, Fabio N.; Pereira, Celia W.; Sánchez-Pérez, Ana M.; Otero-García, Marcos; Ma, Sherie; Gundlach, Andrew L.; Olucha-Bordonau, Francisco E. (Frontiers in Neuroanatomy, 2016)
The neural circuits involved in mediating complex behaviors are being rapidly elucidated using various newly developed and powerful anatomical and molecular techniques, providing insights into the neural basis for anxiety disorders, depression, addiction, and dysfunctional social behaviors. Many of these behaviors and associated physiological processes involve the activation of the amygdala in conjunction with cortical and hippocampal circuits. Ascending subcortical projections provide modulatory inputs to the extended amygdala and its related nodes (or “hubs”) within these key circuits. One such input arises from the nucleus incertus (NI) in the tegmentum, which sends amino acid- and peptide-containing projections throughout the forebrain. Notably, a distinct population of GABAergic NI neurons expresses the highly-conserved neuropeptide, relaxin-3, and relaxin-3 signaling has been implicated in the modulation of reward/motivation and anxiety- and depressive-like behaviors in rodents via actions within the extended amygdala. Thus, a detailed description of the relaxin-3 innervation of the extended amygdala would provide an anatomical framework for an improved understanding of NI and relaxin-3 modulation of these and other specific amygdala-related functions. Therefore, in this study, we examined the distribution of NI projections and relaxin-3-positive elements (axons/fibers/terminals) within the amygdala, relative to the distribution of neurons expressing the calcium-binding proteins, parvalbumin (PV), calretinin (CR) and/or calbindin. Anterograde tracer injections into the NI revealed a topographic distribution of NI efferents within the amygdala that was near identical to the distribution of relaxin-3-immunoreactive fibers. Highest densities of anterogradely-labeled elements and relaxin-3-immunoreactive fibers were observed in the medial nucleus of the amygdala, medial divisions of the bed nucleus of the stria terminalis (BST) and in the endopiriform nucleus. In contrast, sparse anterogradely-labeled and relaxin-3-immunoreactive fibers were observed in other amygdala nuclei, including the lateral, central and basal nuclei, while the nucleus accumbens lacked any innervation. Using synaptophysin as a synaptic marker, we identified relaxin-3 positive synaptic terminals in the medial amygdala, BST and endopiriform nucleus of amygdala. Our findings demonstrate the existence of topographic NI and relaxin-3-containing projections to specific nuclei of the extended amygdala, consistent with a likely role for this putative integrative arousal system in the regulation of amygdala-dependent social and emotional behaviors.